The capture of Pavoloch (1675) – an episode of the Polish–Ottoman war - Malejka, Arkadiusz (Balcanica Posnaniensia. Acta et studia, 2003)
The Polish-Turkish war of 1672–1676 was one of the key conflicts for control over Ukraine. Its main stages and battles have been well described in the literature on the subject, but many episodes remain little known. One of them is the capture of the Pawołocz fortress in March 1675 by Lithuanian troops commanded by Lithuanian Field Hetman Michał Kazimierz Radziwiłł, brother-in-law of King J III Sobieski. The aim of this article is to present this forgotten episode in detail. The author analyses the political and military significance of the capture of the fortress. He emphasises the impact of this event on the operational activities of the Polish army and its propaganda dimension vis-à-vis the Cossacks of Doroshenko and their Turkish allies. The analysis is based on manuscript sources, including royal letters, correspondence between hetmans, reports by envoys, Sejm documents, historical studies and source editions from the 19th and 20th centuries. The method of source analysis and confrontation of accounts from various types of narrative and administrative documents was used. The capture of Pawołocz was not of key strategic importance, but it made it possible to secure communication and military routes in the region of Bracław and Biała Cerkiew. The surrender of the garrison, which included Cossacks and Tatars, strengthened Radziwiłł's authority and provided reinforcements for the Crown's army. Symbolically, this victory showed that the Polish-Lithuanian Commonwealth was able to act effectively under military and political pressure, which also influenced the course of the truce negotiations in Żurawno (1676).